THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK ENVIRONMENT, AND LEADERSHIP ON EMPLOYEE PERFORMANCE IN THE PUBLIC SECTOR - Yanuaria Jeniyanti Bita Seran; Elevenson Nadapdap; Umu Khouroh; Yusaq Tomo Ardianto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study investigates the influence of organizational culture, work environment, and leadership on employee performance within the Regional Secretariat of Malaka Regency, Indonesia. Employing a quantitative approach with a causal research design, data were collected from 139 civil servants using a structured questionnaire. The data were analyzed using multiple linear regression. The findings reveal that both organizational culture and work environment have a significant positive impact on employee performance, particularly when they foster innovation, transparency, and collaboration. Leadership also demonstrates a positive effect, although to a lesser extent compared to the other two variables. The combined effect of the three independent variables accounts for 49.7% of the variation in employee performance. This study provides practical implications for public sector management by emphasizing the need to strengthen organizational culture, create a supportive and conducive work environment, and enhance leadership effectiveness. The findings also contribute to the broader literature on human resource management in government institutions, particularly in emerging economies.